Identification of CCR4C as a chloroplast-localized NADP(H) phosphatase regulating NAD(P)(H) balance in Arabidopsis - Kazuki Akashi; Yutaka Kodama; Hiroaki Sakaguchi; Shin-Nosuke Hashida; Atsuko Miyagi; Toshiki Ishikawa; Masatoshi Yamaguchi; Maki Kawai-Yamada (Proceedings of the National Academy of Sciences, 2025)
NAD(P)(H) metabolism plays a crucial role in plant development and growth. NADK2, a chloroplast-localized NAD kinase, supplies NADP + to the photosynthetic electron transport chain. The Arabidopsis T-DNA insertion mutant of NADK2 ( nadk2 ) exhibits a reduced NADP + /NAD + ratio, slow growth, and pale green leaves. To gain further insights into NAD(P)(H) metabolism in chloroplasts, nadk2 revertant mutants ( nkr ) were screened from the M2 generation of EMS (ethyl methane sulfonate)-treated nadk2 seeds. Among them, nkr1 displayed greener leaves and improved growth compared to nadk2 . Genetic mapping and genomic sequencing identified At3g18500 ( CCR4C ) as the causal gene. The nkr1 mutant carried a single nucleotide substitution, introducing a stop codon within the predicted N-terminal chloroplast localization signal, resulting in the loss of CCR4C protein function. The nadk2 ccr4c double mutant restored leaf color and growth to near wild-type levels. To investigate the function of CCR4C, recombinant CCR4C protein was purified and shown to directly convert NADP(H) to NAD(H). Localization analysis with CCR4C-GFP fusion proteins confirmed chloroplast targeting. Furthermore, ccr4c single mutants exhibited disrupted NAD(P)(H) balance and enhanced tolerance to ROS stress (e.g., H 2 O 2 , methyl viologen). These findings reveal CCR4C as a chloroplast-localized NADP(H) phosphatase crucial for maintaining NAD(P)(H) balance, providing insights into how plant cells manage chloroplast metabolism.